The lncRNA MALAT1/miR-30/Spastin Axis Regulates Hippocampal Neurite Outgrowth - Jiang, Tao; Cai, Zhenbin; Ji, Zhisheng; Zou, Jianyu; Liang, Zhi; Zhang, Guowei; Liang, Yaozhong; Lin, Hongsheng; Tan, Minghui (Frontiers in Cellular Neuroscience, 2020)
Spastin, a microtubule-severing enzyme, is important for neurite outgrowth. However, the mechanisms underlying the post-transcriptional regulation of spastin during microtubule-related processes are largely unknown. We demonstrated that the spastin expression level is controlled by a long non-coding RNA (lncRNA) metastasis-associated lung adenocarcinoma transcript 1 (MALAT1)/microRNA-30 (miR-30) axis during neurite outgrowth. The miR-30 expression level decreased in hippocampal neurons with increasing days in culture, and miR-30 overexpression suppressed while miR-30 inhibition promoted neurite outgrowth in hippocampal neurons. Spastin was validated as a target gene of miR-30 using the luciferase reporter assay. The protein expression, microtubule severing activity and neurite promoting effect of spastin were suppressed by the overexpression of miR-30 mimics and increased by miR-30 inhibitors. MALAT1 expression increased during neurite outgrowth and MALAT1 silencing impaired neurite outgrowth. miR-30 was a sponge target of MALAT1 and MALAT1/miR-30 altered neurite outgrowth in hippocampal neurons. MALAT1 overexpression reversed the inhibitory effect of miR-30 on the activity of a luciferase reporter construct containing spastin, as well as spastin mRNA and protein expression, indicating that spastin was a downstream effector of MALAT1/miR-30. The MALAT1/miR-30 cascade also modulated spastin-induced microtubule severing, and the MALAT1/miR-30/spastin axis regulated neurite outgrowth in hippocampal neurons. This study suggests a new mechanism governing neurite outgrowth in hippocampal neurons involving MALAT1/miR-30-regulated spastin expression.